PENERAPAN MODEL PEMBELAJARAN GENERATIF LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN TIKATAN KIMIA DI KELAS X MIA SMA NEGERI 9 PEKANBARU - Imam Rosidin; Jimmi Copriady; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve the learning outcomes of students on the subject of chemical bonding through the application of learning models Generative Learning in class X SMA Negeri 9 Pekanbaru MIA. Type of research is experimental study using pretest-posttest design. Research conducted at SMAN 9 Pekanbaru. Samples from this study are students of class X MIA2 as an experimental class and the students in class X MIA1 as the control class, this sample was randomly selected after tests of normality and homogeneity in both samples. In the learning process experimental class and control class using the scientific approach to the curriculum beracuan 2013. Classes are classes given experimental treatment using Generative Learning learning model, while the control class is the class that was treated using the usual method implementation discussion. Based on the results of hypothesis testing data analysis obtained t> t table ie 2.99> 1.67, this shows the differences in learning outcomes of students before and after the study material chemical bonds with and without the use of learning model Generative Learning in class X SMA Negeri 9 MIA Pekanbaru. Key Words: Generative Learning, Results Learning, Institute of Chemistry